Microsoft Exchange 2000 infrastructure design : - McCorry, Kieran (Digital Press, 2002)
Microsoft Exchange 2000 Infrastructure Design explains from a system designer's and administrator's perspective Microsoft's Active Directory and its interaction with Exchange 2000, details issues concerned with migration to Exchange 2000, and outlines the specific technology and design issues relating to connectivity with Exchange 2000